The effect of player positional groups on the nature of tackles that result in tackle-related injuries in professional rugby league matches - King, D. A.; Hume, P. A.; Clark, T. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: The aim of this study was to describe the effect of player positional groups on the nature of tackles that result in tackle-related injuries in professional rugby league matches. METHODS:Prospective observational epidemiology analyses for tackle-related injuries and video analyses for the nature of tackles were conducted for a single team in the National Rugby League (NRL) throughout the 2007 and 2008 competitions for a total of 48 games. Risk ratios (RR) were calculated for comparisons between positional groups (adjustable, hit-up forwards or outside backs). RESULTS:The total missed match tackle-related injury rate was 57.8 per 1 000 player hours. Hit-up forwards recorded significantly more total tackle-related injuries than outside backs (RR: 1.3; P=0.049), but not more than adjustables (RR: 1.0; P=0.922). Hit-up forwards recorded significantly more chest-back tackle-related injuries than adjustables (RR: 6.0; P=0.008). Outside backs recorded significantly more tackle injuries as the ball carrier than the tackler (RR: 2.4; P=0.015) while adjustables recorded significantly more tackle injuries as the tackler than the ball carrier (RR: 1.8; P<0.001). Hit-up forwards had a higher incidence of contusions, and sprains while adjustables had a higher incidence of fracture/dislocations. There were no differences in injury severity between the positional groups. CONCLUSION:Player positional group had an effect on tackle-related injury type and injury site. Hit-up forwards and outside backs recorded more tackle-related injuries as a ball carrier than as a tackler, while in contrast, adjustables recorded more tackle-related injuries as the tackler than the ball carrier.